Moderasi Beragama Sebagai Katalisator Untuk Kohesi Sosial Di Desa Puntukdoro Magetan: Religious Moderation as a Catalyst for Social Cohesion in Puntukdoro Village Magetan - Maksum, Muh; Priamono, Gilang Hardiansyah; Mansyuri, Aulya Hamidah; Arifa’i, Muhammad Andiyan (Journal of Community Development and Disaster Management, 2024)
This study explores religious moderation as a catalyst for enhancing social cohesion in Puntukdoro Village, where intolerance towards Christians poses a significant challenge. Data were obtained from primary sources through structured interviews, observations, and documentation, as well as from secondary sources in the form of relevant documents. The data analysis techniques used include data reduction, presentation of data in narrative form, and drawing conclusions. Activities include the "Religious Moderation Goes to School" program, the community event "Religious Moderation Festival," and social media promotion. The results show that these programs successfully increased inclusiveness among children, community participation, and positive public opinion. In conclusion, religious moderation has great potential to build social cohesion and ease tensions in a plural society. Government and social institution support is needed to strengthen diversity and inter-community relationships in Puntukdoro Village. This research provides valuable insights for policies and practices that promote harmony and unity in a multicultural society.